Historical and Future Roles of Internal Atmospheric Variability in Modulating Summertime Greenland Ice Sheet Melt. Issue 6 (20th March 2020) - Sherman, Peter; Tziperman, Eli; Deser, Clara; McElroy, Michael
Abstract: Understanding how internal atmospheric variability affects Greenland ice sheet (GrIS) summertime melting would improve understanding of future sea level rise. We analyze the Community Earth System Model Large Ensemble (CESM‐LE) over 1951–2000 and 2051–2100. We find that internal variability dominates the forced response on short timescales ( 20 years) and that the area impacted by internal variability grows in the future, connecting internal variability and climate change. Unlike prior studies, we do not assume specific patterns of internal variability to affect GrIS melting but derive them from maximum covariance analysis. We find that the North Atlantic Oscillation (NAO) is the major source of internal atmospheric variability associated with GrIS melt conditions in CESM‐LE and reanalysis, with the positive phase (NAO+) linked to widespread cooling over the ice sheet. CESM‐LE and CMIP5 project an increase in the frequency of NAO+ events, suggesting a negative feedback to the GrIS under future climate change. Plain Language Summary: Melting of the Greenland ice sheet is an important anticipated consequence of human‐induced climate change. The human‐induced signal on the Greenland ice sheet can be modulated by internal variability (inherent atmospheric "noise" that arises due to nonlinear processes associated with atmosphere, ocean, and atmosphere‐ocean dynamics). Here, we study historical and future climate simulations to assess the role of summertime internal variability on changes in melting conditions in Greenland. We find that the impact from internal variability changes in the future, which suggests a connection between this atmospheric noise and anthropogenic climate change. We then identify using a statistical technique the patterns of summertime internal variability that are most connected to Greenland ice sheet melting. We find that the North Atlantic Oscillation is the dominant mode of internal atmospheric circulation variability that affects Greenland ice melt conditions, both in the models and observations. Changes in Earth's radiative balance attributable to anthropogenic climate change are found to increase the frequency of positive summertime NAO events in climate models, with significant implications for Greenland's future mass balance. Understanding how these modes of internal variability influence Greenland conditions is an important and necessary step in projecting future changes in the Greenland ice sheet. Key Points: Internal variability plays a dominant role in modulating summertime Greenland ice sheet melt conditions at high frequencies (< 20 years) The North Atlantic Oscillation is the dominant contributor to this modulation and may act as a weak negative feedback on future ice melt Climate change will affect internal variability impacts on Greenland by decreasing its relative importance but increasing its area of impact